Seeing from Below: Scuba Diving and the Regressive Cyborg. Issue 2 (26th December 2020) - Raycraft, Justin
Summary: This article reimagines scuba diving as a form of ethnographic immersion that allows humans to experience life on earth from an underwater perspective. I argue that scuba divers are both posthuman in their cyborgian transcendence of the basic limitations of our species and prehuman in their metaphorical regression into womb‐like oceans, from which all life on earth evolved. I conceptualize divers as (p)reborn humans. Underwater, symbolic modes of human communication devolve to iconic and indexical forms of gesturing that are more in tune with surrounding ecosystems. Scuba diving involves shamanic navigation between lifeworlds, processes that are deeply ritualistic and psychoanalytically significant. Through first‐hand narrative accounts, divers bring new forms of relational knowledge into the public sphere. Bearing in mind the politics of being underwater, I contend that scuba diving can foster a change in how humans apprehend the ocean, from top‐down representation to bottom‐up lived experience. Scuba diving reshapes attention in ways that could inspire collective appreciation for the blue planet that sustains us. Against the backdrop of global environmental change, I call for a shift in the way that humans see and think about the ocean, from above water to below.